The Armenian rebellion at Van - McCarthy, Justin, 1945- (Salt Lake City, Utah : The University of Utah Press, 2006)
Presents a long-overdue examination of the actions at Van, an ancient city in southeastern Anatolia, where the Armenian Revolt is believed to have been a precursor to a great massacre of the people of the East
Contents: List of maps - Acknowledgments - The ruins of Van - The city and province of Van - Allegiance, politics, and power - Rebellion in 1896 - Development of the revolution, 1897-1908 - The Committee of Union and Progress and the Armenians, 1908-1912 - Kurdish revolts and the inspectorates, 1912-1914 - World war I and the Armenian revolt in Van - Destruction and murder in Van - Conclusion - Appendices - Place names -- Armenians in the Van government - Armenian refugees - Extract from the "Instructions for personal defense" (1910) - An example of attacks on villagers - The manifesto of Abdurrezzak - Bibliography - Index.
Includes index
Bibliographical references (p. 286-291)
Keywords: History -- Armenians -- XIX century -- Turkey; Van (Turkey) -- History -- 19th century